Professional Development and Teacher Job Satisfaction: Evidence from a Multilevel Model - Smet, Mike (Mathematics (Basel), 2022)
Numerous studies in different countries find evidence for high rates of teacher turnover, leading to shortages and potential quality issues. Job satisfaction is found to be an important antecedent of turnover. In this study, we investigate the impact of various aspects of professional development for teachers (as well as interactions of these aspects) on job satisfaction. The main goal is to disentangle the interactions between need for and participation in professional development activities, allowing more detailed and precise analyses that may lead to a better substantiated understanding of the mechanisms at work. We use data from the 2018 wave of the OECD’s Teaching and Learning International Survey (TALIS). The hierarchical data structure of teachers nested in schools, nested in regions requires the use of appropriate estimation techniques: multilevel or hierarchical linear modelling (HLM). We find a significant positive relationship between job satisfaction and need for professional development for teaching diversity and special needs, which is (negatively) moderated by the number of professional development activities a teacher had participated in. Another indicator, measuring the need for professional development in subject matter and pedagogy, shows a significant negative relationship with job satisfaction and is (positively) moderated by the amount of professional development.